Chapter Il movimento sindacale, la crisi del fordismo, lo "spazio sociale europeo" - Borioni, Paolo (Studi e saggi, 2023)
The author reconstructs the debate that developed in the 1980s in the Etuc in which Trentin was committed to the construction of a European social model. The essay analyzes the difficulties, contradictions and novelties of the trade union proposal in response to the interconnected effects of inflation, oil crises and mass unemployment in the 1970s, starting with the "Keynes-plus" approach, which proposed new investments for the improvement of working conditions, protection of natural and social environment, and for an equitable distribution of growth and the reduction of consumption of scarce resources, especially energy. Within this framework Trentin stressed the importance of a renewal of the Union's task in post-Fordism in which the European dimension and its ability to affect the process of integration become central.